精密蜗轮副的传动误差测试方法与数据分析 - 郑方燕; 郑永; 陈自然; 高忠华; 董淳 (Jixie chuandong)
A practical measurement method and experimental system of the transmission error measurement for1 worm gear pair is presented.In order to satisfy the requirement of high-speed data acquisition and real-time transport,this system use advanced technology such as FPGA、USB2.0 to make sure of high measurement precision and good repeatability.A precision automatic detection and repeatability measurement method with qualitative mechanic phase-shifting technology is also presented,the system precision can reach ±0.136% and repeatability can reach 0.85″ that can meet the test standard requirement of Level I worm gear pair.